Effect of Irrigation with Diluted Winery Wastewater on Cations and pH in Four Differently Textured Soils - Mulidzi, A.R.; Clarke, C.E.; Myburgh, P.A. (South African Journal of Enology and Viticulture, 2016)
Environmental legislation requires the South African wine industry to find solutions for winery wastewater treatment or reuse. The feasibility of irrigation with diluted winery wastewater was assessed in a pot experiment under a rain shelter over four simulated irrigation seasons. Four soils varying in clay content were irrigated with winery wastewater diluted to 3 000 mg/L chemical oxygen demand (COD), whereas the control received municipal water. The rate of K+ increase in the soil containing 20% clay was higher than in soils containing 13% clay or less. This suggests that heavy soils will aggravate the risk of high K+ levels. The risk of Na+ accumulation increased linearly with clay content. Low Ca2+ and Mg2+ concentrations in the diluted wastewater had no effect on the soil, irrespective of clay content. Irrigation with diluted winery wastewater increased soil pH(KCl) substantially in all the soils over the four simulated seasons. The soil pH increase was attributed to the addition of organic/bicarbonate salts to the soil. It must be noted that the results represent a worst case scenario, i.e. in the absence of rainfall or crops.